Improving Students' Ability in Writing Procedure Text By Using Demonstration Method at SMK 1 TELKOM Medan - Maribet Cicilia Raja Guk Guk; Nurmahyuni Asrul; Dwi Suci Amaniarsih (Departement of Mathematics Education, 2023)
The research used by researchers in this journal is an empirical method that helps researchers monitor teaching and learning processes that take place within the lecture room and take place in two cycles. The researcher used two techniques when conducting the study. The first is a pre-test that is distributed before the study is conducted and the second is a post-test that is distributed after the study is conducted. Aim is to improve student skills learn how to create procedural texts using demonstration methods in her SMK Telkom 1 Medan im Studienjahr 2022/2023. The sample drawn was her 32 students in class X TKJ 2. Improvements in student great writing skills in student learning outcomes verified by post-tests. Increased from cycle 1 to cycle 2. On pre-testing earlier than Cycle 1 became introduced, 14 of her students failed Passing marks (KKM) for 32 students. So class X-TKJ 2 SMK Telekom 1 had 18 students. Medan where you KKM can be passed later going through the exams. In cycle 1, 11 students failed the test, and in cycle 2, 3 students failed his KKM, which uses demonstration methods to create procedural texts. In another sense, it is said that 18 students passed cycle 1, 21 students passed cycle 1, and 29 students passed successfully completed cycle 2. Additionally, improve students make This research is supported by others studies and theories.